STRATEGI PENGEMBANGAN USAHATANI LADA DI KECAMATAN PALOH KABUPATEN SAMBAS - Afi, Nur Diyanah; Kurniati, Dewi; Suyatno, Adi (Universitas Galuh, 2023)
One of the leading commodities in the plantation sub-sector in West Kalimantan is pepper (Piper nigrum L). Total pepper production in 2020 is 4,970 tonnes. In 2021, the pepper planting area in West Kalimantan will have increased by 36.49%, with a total production of 476 tons. Paloh District is an area that has a planting area of 471 hectares and the lowest productivity of 0.28 metric tons. This study aims to formulate a strategy for the development of pepper farming in Paloh District, Sambas Regency. SWOT analysis was used in this research methodology with 43 respondents who were taken using a purposive sampling method. The results showed that the biggest internal factors were the strength, namely the availability of farming land, and the weakness, namely the lack of fertilizer. While the biggest opportunity factor is pepper, which is an export product with the threat of falling pepper prices.